Psychosocial burden and healthcare disillusionment in recurrent UTI: a large-scale international survey of patient perspectives - Maxwell, Kayleigh; Roberts, Lindsey; Kramer, Melissa; Price, Jessica; Newlands, Abigail; Finlay, Katherine A. (Frontiers in Urology, 2023)
Objectives: Recurrent UTI (rUTI) is a debilitating health condition associated with persistent mental, physical, and social burden. People living with rUTI face inconsistencies in diagnostic testing and fragmented treatment pathways, alongside their symptoms, likely adding considerably to illnessrelated burden. This study aimed to characterize the factors negatively impacting this population from the qualitative perspectives of people living with the condition.Methods: Qualitative data was collected via free-text responses using an online survey hosted by an rUTI patient advocacy website. Female participants with self-reported rUTI (n = 1,983) described factors most salient to their experiences living with the condition. Data was analyzed using a coding reliability approach to thematic analysis.Results: Two overarching themes were identified: (1) the patient burden of rUTI, which describes the multifaceted biopsychosocial impact of the illness, and (2) healthcare disillusionment, which describes patient dissatisfaction with healthcare received, both in terms of treatments offered and communication with healthcare professionals. The patient burden of rUTI encompassed four subordinate themes: facing ongoing uncertainty, symptom salience, sex is not simple anymore, and perceived UTI stigma. Healthcare disillusionment included three subordinate themes: discomfort with frequent antibiotic use, fragmented treatment pathways, and devalued patient perspectives.The findings demonstrated that ambiguity in the diagnosis of rUTI and inconsistencies in the subsequent treatment pathway are exacerbated by poor patient-clinician communication. The extent of the female-specific burden of rUTI symptoms confirmed the harmful effects of facing illness-related stigma. This novel qualitative reporting of rUTI symptom burden and life impact highlights the urgent need for increased patient-centered care for those living with rUTI. More effective rUTI management could have a major impact on treatment outcomes and patient-reported psychosocial wellbeing.